Complete genome sequence of Halorhodospira halophila SL1. Issue 2 (March 2013) - Challacombe, Jean; Majid, Sophia; Deole, Ratnakar; Brettin, Thomas; Bruce, David; Delano, Susana; Detter, John; Gleasner, Cheryl; Han, Cliff; Misra, Monica; Reitenga, Krista; Mikhailova, Natalia; et al.
Abstract Halorhodospira halophila is among the most halophilic organisms known. It is an obligately photosynthetic and anaerobic purple sulfur bacterium that exhibits autotrophic growth up to saturated NaCl concentrations. The type strainH. halophila SL1 was isolated from a hypersaline lake in Oregon. Here we report the determination of its entire genome in a single contig. This is the first genome of a phototrophic extreme halophile. The genome consists of 2, 678, 452 bp, encoding 2, 493 predicted genes as determined by automated genome annotation. Of the 2, 407 predicted proteins, 1, 905 were assigned to a putative function. Future detailed analysis of this genome promises to yield insights into the halophilic adaptations of this organism, its ability for photoautotrophic growth under extreme conditions, and its characteristic sulfur metabolism.